Pengaruh Orientasi Perbandingan Sosial, Kecerdaan Spiritual Dan Efikasi Diri Terhadap Pengelolaan Keuangan Mahasiswa Akuntansi Batam - Tri Adinda Rahmawati; Erni Yanti Natalia (Jurnal Liabilitas, 2026)
The rapid development of digital technology and the ease of access to financial services such as digital banking, e-wallets, and paylater systems pose challenges for students in managing personal finances. Although accounting students academically possess financial knowledge, in practice many of them still demonstrate inadequate financial management behavior. This behavior is influenced by several psychological and social factors, including social comparison orientation, spiritual intelligence, and financial self-efficacy. This study aims to analyze the effect of social comparison orientation, spiritual intelligence, and financial self-efficacy on the financial management behavior of accounting students in Batam City, both partially and simultaneously. This research employed a quantitative method with a descriptive-associative research design. Data were collected through an online questionnaire distributed via Google Form to accounting students at Universitas Internasional Batam, Universitas Universal, and Universitas Ibnu Sina. The sampling technique used was non-probability sampling with a quota sampling method, involving 152 respondents. The measurement instrument used a Likert scale, and the data were analyzed using multiple linear regression analysis. The results indicate that social comparison orientation, spiritual intelligence, and financial self-efficacy have a significant effect on students’ financial management behavior, both individually and simultaneously. This study concludes that psychological and social factors play an important role in shaping the financial management behavior of accounting students in Batam City.